Legal and Bioethical Implications of Do Not Resuscitate (DNR) by Doctors in Indonesia - Sarana, Harmin; Sutarno , Sutarno; Prasetyo, Boedi (Manunggal Halim Jaya, 2025)
This paper examines the legal and bioethical implications of Do Not Resuscitate (DNR) decisions made by physicians in Indonesia, using a juridical and literature analysis approach. DNR decisions, which involve withholding or discontinuing life-sustaining treatment, are complex and fraught with legal, ethical, and cultural challenges. In Indonesia, the lack of explicit legal guidance regarding DNR creates significant ambiguity for healthcare professionals. This paper examines the relationship between the legal framework, medical ethics, and cultural influences that shape these decisions. It highlights the role of autonomy, beneficence, impartiality, and justice in ethical considerations surrounding DNR. Furthermore, it considers the influence of Indonesia's largely religious and collectivist culture, which often places family decisions above patient autonomy. Through a literature review and legal analysis, this paper suggests the need for clearer guidelines and greater protections for healthcare providers involved in DNR decisions. It also proposes enhanced bioethics education for medical professionals and increased public awareness of patient rights in end-of-life care.